D2.2. LITES luminaires produced - Larat, Emmanuel (2014)
The Deliverable D2.2. “LITES luminaires produced” deals with Task 2.3. “Toolkits fabrication for luminaires’ production” and Task 2.4. “Production of the final LITES luminaires”. The objective of this Deliverable is to allow preparing the embedding of all LITES subsystems (power supply, sensors, antenna, etc...), Integrate of all the subcomponents into the luminaires and check (test) the mechanical, electrical and optical performance of each luminaire before shipment to the Pilot Site shipping address (see Deliverable 8.1). The final element selection and tests allow also developing installation documentation that is described in Deliverable 2.3.